Degeneracy of the 1/8 plateau and antiferromagnetic phases in the Shastry-Sutherland magnet TmB4 - Trinh, Jennifer (2019)
The 1/8 fractional plateau phase (1/8 FPP) in Shastry-Sutherland lattice (SSL) spin systems has been viewed an exemplar of emergence on an Archimedean lattice. Here we explore this phase in the Ising magnet TmB4 using high-resolution specific heat (C) and magnetization (M) in the field-temperature plane. We show that the 1/8 FPP is smoothly connected to the antiferromagnetic phase on ramping the field from H=0. Thus, the 1/8 FPP is not a distinct thermodynamic ground state of TmB4. The implication of these results for Heisenberg spins on the SSL is discussed.